Macrogenomes reveal microbial-mediated microplastic degradation pathways in the porcine gut: a hope for solving the environmental challenges of microplastics - Wang, Tao; Luo, Yuheng; Yu, Bing; Zheng, Ping; Huang, Zhiqing; Mao, Xiangbing; Yu, Jie; Luo, Junqiu; Yan, Hui; He, Jun (Frontiers in Microbiology, 2024)
It is increasingly recognized that microplastics (MPs) are being transmitted through the food chain system, but little is known about the microorganisms involved in MP degradation, functional biodegradation genes, and metabolic pathways of degradation in the intestinal tract of foodborne animals. In this study, we explored the potential flora mainly involved in MP degradation in the intestinal tracts of Taoyuan, Duroc, and Xiangcun pigs by macrogenomics, screened relevant MP degradation genes, and identified key enzymes and their mechanisms. The pig colon was enriched with abundant MP degradation-related genes, and gut microorganisms were their main hosts. The fiber diet did not significantly affect the abundance of MP degradation-related genes but significantly reduced their diversity. We identified a total of 94 functional genes for MP degradation and classified them into 27 categories by substrate type, with polystyrene (PS), polyethylene terephthalate (PET), and di(2-ethylhexyl) phthalate (DEHP) were the most predominant degradation types. The MP degradation functional genes were widely distributed in a variety of bacteria, mainly in the phylum Firmicutes and Bacteroidetes. Based on the identified functional genes for MP degradation, we proposed a hypothetical degradation mechanism for the three major MP pollutants, namely, PS, PET, and DEHP, which mainly consist of oxidoreductase, hydrolase, transferase, ligase, laccase, and isomerase. The degradation process involves the breakdown of long polymer chains, the oxidation of short-chain oligomers, the conversion of catechols, and the achievement of complete mineralization. Our findings provide insights into the function of MP degradation genes and their host microorganisms in the porcine colon.